ANALYSIS OF STOCK MARKET REACTION TO LARGESCALE SOCIAL RESTRICTIONS POLICY ANNOUNCEMENT - Luckman, Aliakito; Mulyani, Erly (Berkala Akuntansi dan Keuangan Indonesia, 2022)
This study aims to analyze stock market reactions to large-scale social restrictions policy implementation announcements. The method used is event study. This study used 7, 5, and 3 days event window and 120 days estimation window for calculating abnormal return. The samples of this study are 32 companies in the tourism, hotel, and restaurant sub-sector listed in Indonesia Stock Market which were determined by purposive sampling method. The results of this study indicate that 1) there was no significant negative market reaction indicated by negative and insignificant average abnormal return and accumulation average abnormal return around the announcement date of the Large-Scale Social Restrictions (PSBB) policy implementation which means that the market does not react to the event and 2) there was no significant difference in average abnormal return before and after the announcement of the Large-Scale Social Restrictions (PSBB) policy implementation.